ANALISIS WACANA PRAGMATIK TINDAK TUTUR DAN DAN IMPLIKATUR DALAM RUBIK POS PEMBACA PADA HARIAN SOLOPOS EDISI 20 NOVEMBER 2025 - Doni Uji Windiatmoko (Indonesian language and literature education program Majapahit Islamic University, 2025)
This study aims to describe the forms of locutionary, illocutionary, perlocutionary, and implicature speech acts in the